Interference-based optical image encryption with silhouette removal by amplitude modulation. (30th August 2017) - Wang, Yong; Quan, Chenggen
Abstract: Interference-based optical encryption schemes have an inherent silhouette problem, due to the equipollent nature of the phase-only masks generated from an analytical method. We propose a new interference-based optical image encryption with silhouette removal by amplitude modulation. Different from the previous methods, which require time-consuming iterative computation or post-processing of the phase-only masks for silhouette removal, the proposed method can resolve the problem by adding an amplitude modulating operation on the original image. The introduction of the amplitude modulator can significantly enhance the security of the system, and the silhouette problem inherent in a conventional interference-based encryption method is fully resolved. The design and parameter choice of the amplitude modulator is discussed. Numerical simulations are presented to verify the validity of the proposed method.